A PLEA FOR CULTURE-INTEGRATED LANGUAGE TEACHING - ATAMNA, Elkhiar (Journal of Human Sciences, 2008)
ATAMNA ElkhiarDépartement d’AnglaisUniversité Mentouri Constantine  (Algérie)  Foreign language teaching no longer focuses on the development of the learners’ linguistic competence only. It has also set itself the aim to develop their intercultural communicative competence. The observation that this aim is feasible constitutes the rationale for the present paper which argues for a place for culture teaching within the English course syllabus in the English Department at the University Mentouri,Constantine,Algeria.